2012
DOI: 10.1111/j.1478-3231.2011.02735.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of 25‐hydroxyvitamin D levels with liver dysfunction and mortality in chronic liver disease

Abstract: Our findings show a significant association of 25(OH)D with the degree of liver dysfunction and suggest that low 25(OH)D levels may predict hepatic decompensation and mortality in patients with chronic liver failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
82
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 34 publications
(72 reference statements)
13
82
2
1
Order By: Relevance
“…These results are in agreement with other studies (17,18,19) on (8). Other studies demonstrated the lower serum vitamin D levels, the higher the degree of inflammation and/or stage of fibrosis in chronic HCV patients (15,20,21,22). Arteh et al (23) reported that vitamin D <32 ng/mL was detected in 92% of 118 patients with CLD.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with other studies (17,18,19) on (8). Other studies demonstrated the lower serum vitamin D levels, the higher the degree of inflammation and/or stage of fibrosis in chronic HCV patients (15,20,21,22). Arteh et al (23) reported that vitamin D <32 ng/mL was detected in 92% of 118 patients with CLD.…”
Section: Discussionsupporting
confidence: 82%
“…In this single center study, we show that low vitamin D levels are common in patients with cirrhosis, as demonstrated in previous studies (6,7,9,(26)(27)(28). However, the prevalence of low vitamin levels, defined as 25(OH)D levels <20 ng/ml, was less than many previous studies (7,(26)(27)(28), which may be due to higher use of vitamin D supplementation and lower disease severity in our patient population.…”
Section: Discussionsupporting
confidence: 75%
“…This is because of most of cases in our study belonged , Putz-Bankuti C et al 19 and Finkelmeier F et al 22 We also found low vitamin D level was associated with poor outcome similar to Finkelmeier F et al 22 Thus our results suggest that vitamin D might be both a biomarker of severity and a potential therapeutic target in CLD.…”
Section: Discussionsupporting
confidence: 69%
“…We found low prevalence of CLD in Females in contrast to earlier study done by Putz Bankuti C et al, 19 which consists of 51 males (68%) and 24 females (32%) with a mean age of 58 ± 11 years (range: 25-89 years).…”
Section: Discussioncontrasting
confidence: 55%